2018
DOI: 10.1007/s00520-018-4243-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the measurement properties of the European Organisation for Research and Treatment of Cancer In-patient Satisfaction with Care Questionnaire, the EORTC IN-PATSAT32

Abstract: PurposeThe EORTC IN-PATSAT32 is a patient-reported outcome measure (PROM) to assess cancer patients’ satisfaction with in-patient health care. The aim of this study was to investigate whether the initial good measurement properties of the IN-PATSAT32 are confirmed in new studies.MethodsWithin the scope of a larger systematic review study (Prospero ID 42017057237), a systematic search was performed of Embase, Medline, PsycINFO, and Web of Science for studies that investigated measurement properties of the IN-PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…É importante, contudo, ressaltar que há marcadas diferenças, nesses aspectos, entre Brasil e esses países, principalmente considerando a natureza do sistema de saúde (no caso brasileiro, universal e gratuito), as questões culturais (que definem, no limite, o enfrentamento da doença). Uma recente revisão sistemática 32 destacou a validade desse instrumento em distintos contextos. Contudo, o Brasil não esteve incluído neste estudo, possivelmente pelo fato de o estudo de validação, assim como o estudo no Marrocos 33 , terem sido publicados posteriormente ao protocolo daquela revisão.…”
Section: Discussionunclassified
“…É importante, contudo, ressaltar que há marcadas diferenças, nesses aspectos, entre Brasil e esses países, principalmente considerando a natureza do sistema de saúde (no caso brasileiro, universal e gratuito), as questões culturais (que definem, no limite, o enfrentamento da doença). Uma recente revisão sistemática 32 destacou a validade desse instrumento em distintos contextos. Contudo, o Brasil não esteve incluído neste estudo, possivelmente pelo fato de o estudo de validação, assim como o estudo no Marrocos 33 , terem sido publicados posteriormente ao protocolo daquela revisão.…”
Section: Discussionunclassified
“…Patients and clinicians will complete the PSSUQ, a validated 16-item survey to assess the perceived learnability, efficiency, and errors of H2T, as well as user satisfaction with the app [ 20 , 22 ] (see Multimedia Appendix 1 ). Patients will also submit a survey to assess their satisfaction with their postoperative care at postoperative day 30 to assess their perceived experience of their postdischarge care using a modified version of PATSAT32, a validated questionnaire for patients undergoing gastrointestinal surgery [ 23 , 24 ] (see Multimedia Appendix 1 ). The intervention will be reviewed every two months by the investigator team and General Surgery Comprehensive Unit-based Safety Program team.…”
Section: Methodsmentioning
confidence: 99%
“…[39] and Pishkuhi et al [38] as has been shown by Neijenhuijs et al [29]. However, as no minimal important change has been defined for the EORTC IN-PATSAT32 an overall rating of the measurement error is not possible.…”
Section: Analysis Of Measurement Errormentioning
confidence: 99%
“…Neijenhuijs et al[29]. ICC was ≥0.70 for all subscales of the EORTC IN-PATSAT32 in the study by Pishkuhi et al In the study by Obtel et al all scales except doctor availability Results of reliability analyses of German-language PREMs.…”
mentioning
confidence: 96%
See 1 more Smart Citation